Land, trees, and women: evolution of land tenure institutions in Western Ghana and Sumatra - Quisumbing, Agnes R.; Otsuka, Keijiro (International Food Policy Research Institute, 2001)
This research report examines three questions that are central to IFPRI research: How do property-rights institutions affect efficiency and equity? How are resources allocated within households? Why does this matter from a policy perspective? As part of a larger multicountry study on property rights to land and trees, this study focuses on the evolution from customary land tenure with communal ownership toward individualized rights, and how this shift affects women and men differently.This study’s key contribution is its multilevel econometric analysis of efficiency and equity issues. Using a combination of community, village, and household surveys in Western Ghana and Sumatra, two areas with traditional matrilineal inheritance systems, the authors and their collaborators analyze the effectiveness of village-, household-, and parcel-level property-rights institutions and arrangements.